Body composition estimates from bioelectrical impedance and its association with cardiovascular risk - Jesne Kistan; Jeffrey Wing; Khanyisile Tshabalala; Wesley van Hougenhouck-Tulleken; Debashis Basu (African Journal of Primary Health Care & Family Medicine)
Background: Screening for traditional risk factors of cardiovascular disease is well known in primary healthcare (PHC) settings. However, other risk factors through newer tools (such as bioelectrical impedance analysis [BIA]) could also be predictors of increased cardiovascular risk (CVR). Body composition estimates (body fat percentage, body water percentage, body lean mass) by BIA and its association to CVR have been studied with variable results.